Fluoride and aluminum in teas and tea-based beverages - Mitsue Fujimaki Hayacibara; Celso Silva Queiroz; Cínthia Pereira Machado Tabchoury; Jaime Aparecido Cury (Universidade de São Paulo, 2004)
OBJECTIVE: To evaluate fluoride and aluminum concentration in herbal, black, ready-to-drink, and imported teas available in Brazil considering the risks fluoride and aluminum pose to oral and general health, respectively. METHODS: One-hundred and seventy-seven samples of herbal and black tea, 11 types of imported tea and 21 samples of ready-to-drink tea were divided into four groups: I-herbal tea; II-Brazilian black tea (Camellia sinensis); III-imported tea (Camellia sinensis); IV-ready-to-drink tea-based beverages. Fluoride and aluminum were analyzed using ion-selective electrode and atomic absorption, respectively. RESULTS: Fluoride and aluminum levels in herbal teas were very low, but high amounts were found in black and ready-to-drink teas. Aluminum found in all samples analyzed can be considered safe to general health. However, considering 0.07 mg F/kg/day as the upper limit of fluoride intake with regard to undesirable dental fluorosis, some teas exceed the daily intake limit for children. CONCLUSIONS: Brazilian and imported teas made from Camellia sinensis as well as some tea-based beverages are sources of significant amounts of fluoride, and their intake may increase the risk of developing dental fluorosis.